Silent Scenes in Manga as the Powerful and Universal Visual Languages - Hafiz Aziz Ahmad (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2012)
Comics as the popular medium of communication, especially medium for the children due to its capabilities in telling stories with its visual narrative has been known for quite long. Manga as the form of comic medium that came from Japan is also well known for its uniqueness. Due to the strong relation within the Japan cultural background, manga has integrated its own distinctive way in telling the stories, visually. One of the methods is known as the silent sequences. The silent sequences term is used to mention the scene in comics that told using minimal sequence and with very little -if any- text or narration. Some even used several of unconnected scenes to create a specific mood or a sense of place. Such scenes could be found in abundance in various manga works, notably in the works of Osamu Tezuka or Mitsuru Adachi. Scott McCloud